MENGOPTIMALKAN POTENSI LOKAL: STRATEGI PENGEMBANGAN USAHA KERUPUK UBI KAYU DI DESA KELE’I - Kolompo, Septian Aditya; Guampe, Feliks Arfid (Gapenas Publisher, 2024)
This study aims to analyze the opportunities and development strategies for cassava cracker businesses in Kele’i Village, Poso Regency. The research employed a descriptive qualitative approach with SWOT analysis to identify internal and external factors influencing the business. Data were collected through interviews, observations, and literature review, involving 15 business operators as respondents. The findings indicate that the cassava cracker business in Kele’i Village is positioned in Quadrant I of the SWOT analysis, suggesting strong internal factors and significant opportunities for growth. Key strengths include high product quality, affordable pricing, and a variety of preservative-free products. However, challenges such as unattractive packaging and ineffective promotion require attention. Opportunities include increasing market demand, government support, and the rise of digital promotion, while threats from new competitors and substitute products persist. The recommended strategies involve utilizing modern technology to enhance production efficiency, diversifying products to target broader market segments, and strengthening promotion through social media. Collaboration with the government is also advised to support technical training and provide production equipment. This study concludes that developing the cassava cracker business requires technological innovation, effective marketing strategies, and collaboration with various stakeholders to ensure sustainability and competitiveness in both local and national markets